2020
DOI: 10.1088/1748-605x/ab316a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the in vivo biocompatibility and performance of freeze-cast tissue scaffolds

Abstract: Quantitative methods are little used for the in vivo assessment of tissue scaffolds to evaluate biocompatibility. To complement current histological techniques, we introduce as a measure of biocompatibility a straightforward, geometric analysis for the quantitative assessment of encapsulation thickness, cross-sectional area, and biomaterial shape. Advantages of this new technique are that it enables, on the one hand, a more complete and objective comparison of scaffolds with differing compositions, architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
2
1
Order By: Relevance
“…The design and functionalization of the scaffold impact the expression of the immune response produced after implantation, resulting in variations in the size of the capsule surrounding the biomaterial. The capsule size recorded in our investigation, as shown in Figure 5B, is smaller than that reported by other studies (Divakar et al, 2020), where a capsule thickness of 3 mm was observed around scaffolds made from unfunctionalized collagen. Results similar to those obtained in our investigation were also reported (Dulany et al, 2020;Camarero-Espinosa et al, 2022).…”
Section: Discussioncontrasting
confidence: 87%
“…The design and functionalization of the scaffold impact the expression of the immune response produced after implantation, resulting in variations in the size of the capsule surrounding the biomaterial. The capsule size recorded in our investigation, as shown in Figure 5B, is smaller than that reported by other studies (Divakar et al, 2020), where a capsule thickness of 3 mm was observed around scaffolds made from unfunctionalized collagen. Results similar to those obtained in our investigation were also reported (Dulany et al, 2020;Camarero-Espinosa et al, 2022).…”
Section: Discussioncontrasting
confidence: 87%
“…An example for a biomedical application of chitosan-based tissue scaffolds are freeze-cast shell-only and core–shell conduits for peripheral nerve repair. ,, In addition to the highly aligned porosity, the ridges in the pure chitosan scaffolds assist in neurite guidance. The addition of CNF increases the scaffolds’ mechanical properties and through these the resilience, when handled and secured in place with a stitch or glue by a surgeon, for example. Additionally, the fibrillar pillars and bridges in the Chi–CNF help preserve the pore structure, also when laterally compressed during surgery and implantation; , similar structural benefits in freeze-cast scaffolds made from fibrillar components were observed in vivo for collagen …”
Section: Resultsmentioning
confidence: 80%
“…More recently, collagen was freeze cast to create scaffolds for permanent female sterilization that was tested on successfully with rats . The effect of processing conditions was further tested and showed that lower freezing rate produced larger pores and thicker lamellar walls, resulting in decreased modulus but higher yield strength . Across multiple materials, freeze casting has showed promise for creating controlled micro‐ and macroporosity.…”
Section: Bioinspired Designs At Different Length‐scalesmentioning
confidence: 99%